Cosmology and the Problem of Evil: God and the Second Law - Cahoone, Lawrence E. (Zygon, 2025)
For decades, a discussion has raged over the explanation of the peculiarity of our universe due to its fine-tuned constants. One explanation is that ours is one of an infinite number of randomly produced universes. Another is that a beginningless ground of nature or God produced our universe. The most serious argument against the notion of a God remains the problem of evil. But the same century that produced the idea of an evolutionary universe produced a "process" notion of God, rejecting omnipotence and omniscience and making God partly corporeal. The question lying behind the discussion of fine-tuned constants is what could have caused this particular universe, a world of order, disorder, and hazard, which took ten billion years to produce the local complexities of life and mind. One explanation is a God subject to internal limitations that apply to the universe as well. Such a Ground of Nature is likely not only to be partly physical but also subject to the laws of thermodynamics.